Compaction and strength characteristics of a compacted residual soil - Weeraratne, Saroj Premasiri; Prinzl, Frediric; Yudhbir; Balasubramaniam, A.S.; Government of Denmark (Bangkok : Asian Institute of Technology, 1982)
A detailed investigation is made into the influence of compaction at different moisture contents on the soil structure, undrained strength, stress-strain characteristics, effect of aging, soil suction pressures as well as erodibility, of a residual soil at the Chiew larn dam site. As a preliminary investigation physical properties of this soil, viz: particle size distribution, specific gravity and Atterberg limits were carried out. The correlations between the maximum dry density and optimum moisture content, optimum moisture content and plastic limit, that has been established for mineral mixtures and natural soils, seem to be applicable to this soil. An analysis was made on the drying process as a possible way to study the influence of structure on the compacted soil behavior. An investigation was carried out to check the validity of a simple method proposed by Marsal to evaluate the effective stress parameters of compacted soils, and the results are satisfactory with the Values obtained using conventional methods. Finally pinhole tests were carried around optimum moisture content to investigate the influence of moisture content and soil structure on the dispensability of the soil and Sodium analysis as a supplementary test. Both these tests identified the soil as nondispersive.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Soil mechanics